2006
DOI: 10.1002/ajmg.a.31456
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mosaicism for an HRAS mutation causes Costello syndrome

Abstract: De novo heterozygous HRAS point mutations have been reported in more than 81 patients with Costello syndrome (CS), but genotype/phenotype correlation remains incomplete because the majority of patients share a common mutation, G12S, seen in 65/81 (80%). Somatic HRAS mutations have previously been identified in solid tumors, and mutation hot spots related to a gain-of-function effect of the gene product are known. The germline mutations causing CS occur at these hot spots and convey a gain-of-function effect, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 20 publications
6
67
0
2
Order By: Relevance
“…Activating mutations of the tyrosine phosphatase SHP2, HRas, B-Raf, and MEK1/2 were found in Noonan syndrome, Costello syndrome, and cardiofaciocutaneous syndrome. 10,[41][42][43][44][45] The common features of these syndromes, include hypertrophic cardiomyopathy, electrophysiological abnormalities, and septal defects. 46 Although a gain-of-function mutation of Ras signaling is believed to be the underlying mechanism for congenital heart disease, emerging evidence from clinical and genetic studies have revealed that downregulation of Ras/ERK singling is also associated with cardiac defects during development.…”
Section: Ras Signaling Pathway In Heart Developmentmentioning
confidence: 99%
“…Activating mutations of the tyrosine phosphatase SHP2, HRas, B-Raf, and MEK1/2 were found in Noonan syndrome, Costello syndrome, and cardiofaciocutaneous syndrome. 10,[41][42][43][44][45] The common features of these syndromes, include hypertrophic cardiomyopathy, electrophysiological abnormalities, and septal defects. 46 Although a gain-of-function mutation of Ras signaling is believed to be the underlying mechanism for congenital heart disease, emerging evidence from clinical and genetic studies have revealed that downregulation of Ras/ERK singling is also associated with cardiac defects during development.…”
Section: Ras Signaling Pathway In Heart Developmentmentioning
confidence: 99%
“…Atypical findings included microcephaly, streaky areas of skin hypo-and hyperpigmentation, and normal menarche with subsequent regular menses. 44 Somatic mosaicism was seen in a father who showed a patchy distribution of skin findings suggestive of Costello syndrome and who transmitted the p.Gly12Ser change to his son with typical Costello syndrome. 13 Mosaicism for the p.Gly12Ser mutation was noted in an individual with a typical presentation including apparent cutis laxa.…”
Section: Introductionmentioning
confidence: 99%
“…14 As may be expected in an autosomal dominant trait, somatic mosaicism can thus be associated with a range of findings including patchy or segmental distribution, typical phenotypic presentation, and transmission to offspring and recurrence in siblings. 44 …”
Section: Introductionmentioning
confidence: 99%
“…Later reports confirmed the presence of HRAS codon 12 and 13 mutations in 85-90% of Costello syndrome patients with G12S being the most prevalent mutation and G12A the second most prevalent [14,17,26]. One report described somatic mosaicism for an HRAS codon 12 mutation [19]. As mentioned before, these mutations derange RAS GTP-ase activity and cause activation of the RAS MAPK pathway.…”
Section: Neurofibromatosis Type 1 (Omim 162200)mentioning
confidence: 69%